Framing Political Legitimacy after the 2024 Indonesian Presidential Election: A Comparative Analysis of Detik.com and Kompas.com - Nasrullah (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2026)
This study examines how mainstream online media construct the narrative of the victory of presidential candidate pair number 02 in Indonesia’s 2024 Presidential Election (Prabowo Subianto – Gibran Rakabuming Raka). The analysis focuses on post-election coverage published by Detik.com and Kompas.com, employing Robert N. Entman’s framing model with four key elements: define problems, diagnose causes, make moral judgments, and suggest remedies. The data consist of six news articles published between 14 February–21 March 2024. The findings reveal that Detik.com tends to frame the victory of candidate pair 02 affirmatively, emphasizing electoral legitimacy and institutional support. In contrast, Kompas.com highlights democratic concerns, public criticism, and expectations regarding future governance. These framing differences reflect the editorial orientations and audience segmentation of each outlet. The study argues that post-election news coverage is not merely about reporting vote counts but also about constructing political legitimacy within the digital public sphere. This research contributes to media and political communication studies by demonstrating how online media framing shapes public opinion and reinforces or challenges political victory narratives in Indonesia’s digital democracy.